New seamount- and ridge-associated cyclostome Bryozoa from New Zealand - Gordon, Dennis P.; Taylor, Paul D. (Zootaxa, 2010)
Recent sampling of seamount and ridge habitats in the New Zealand Exclusive Economic Zone has yielded new cyclostome bryozoan taxa. We describe here one new genus, a new name, Dartevellopora (to replace the generic homonym Dartevellia Borg, 1944) and ten new species, comprising Filicisparsa albobrunnea n. sp. (Oncousoeciidae), Discantenna tumba n. gen., n. sp. (Diastoporidae), Supercytis gracilis n. sp. (family incertae sedis), Filifascigera brevicaudex (Frondiporidae); Plagioecia parva n. sp. (Plagioeciidae), Favosipora bathyalis n. sp. (Densiporidae), and Dartevellopora neozelanica n. sp., D. rugosa n. sp., Disporella minicamera and D. minutissima n. sp. (Lichenoporidae). Seven of the new species occurred in the “Graveyard Seamount Complex” on the north-central Chatham Rise to the east of the South Island. Of these, three species and one new genus are known only from the type locality on “Graveyard” Seamount ― the most intensively fished of the seamounts in the complex by heavy bottom-trawl gear, which has implications for species conservation. Evidence based on discrimination between benthic invertebrate assemblages of hard bottoms on fished and unfished seamounts in the area suggests that small, short-lived taxa like cyclostome bryozoans might not be disadvantaged by bottom-trawling.